2008
DOI: 10.3892/or.19.4.999
|View full text |Cite
|
Sign up to set email alerts
|

ATR alterations in Hodgkin's lymphoma

Abstract: Hodgkin's lymphoma (HL) is characterized by the presence of neoplastic Hodgkin and Reed-Sternberg cells (HRSC) in a background of inflammatory cells. Free radicals and oxidative stress generated in the inflammatory lesions could cause DNA damage, thus providing a basis for lymphomagenesis. Ataxia-telangiectasia mutated (ATM) and Rad3-related (ATR) genes are responsive genes for DNA damage, therefore the potential involvement of the ATR gene in HL pathogenesis was examined in 8 HL cell lines and 7 clinical case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In particular, in ATM, distinct mutations have been found that cause different human malignancies, including lung cancer, breast cancer, colon cancer, lymphocytic leukemia, pancreatic cancer, and head and neck cancer, among others (Ding et al, 2008;Goldgar et al, 2011;Guarini et al, 2012;Roberts et al, 2012;Seshagiri et al, 2012) (see poster). Homozygous loss-of-function mutations or deletion of ATR or Chk1 have not yet been reported; however, there are sporadic studies that show mutations in ATR or Chk1 in certain cancer types (Kim et al, 2007;Lewis et al, 2007;Liu et al, 2008;Menoyo et al, 2001;Zighelboim et al, 2009) (see poster), suggesting that the ATRChk1 axis cannot be generalized as a canonical tumor suppressor pathway.…”
Section: Box 1 Relevance Of Atm and Atr Signaling In Cancermentioning
confidence: 99%
“…In particular, in ATM, distinct mutations have been found that cause different human malignancies, including lung cancer, breast cancer, colon cancer, lymphocytic leukemia, pancreatic cancer, and head and neck cancer, among others (Ding et al, 2008;Goldgar et al, 2011;Guarini et al, 2012;Roberts et al, 2012;Seshagiri et al, 2012) (see poster). Homozygous loss-of-function mutations or deletion of ATR or Chk1 have not yet been reported; however, there are sporadic studies that show mutations in ATR or Chk1 in certain cancer types (Kim et al, 2007;Lewis et al, 2007;Liu et al, 2008;Menoyo et al, 2001;Zighelboim et al, 2009) (see poster), suggesting that the ATRChk1 axis cannot be generalized as a canonical tumor suppressor pathway.…”
Section: Box 1 Relevance Of Atm and Atr Signaling In Cancermentioning
confidence: 99%
“…ATR kinases play an important role in maintaining genome integrity during DNA replication through the phosphorylation and activation of Chk1 and regulation of the DNA damage response. Only one study [ 78 ] has examined ATR gene alterations in eight HL cell lines and in seven clinical cases. Alterations of ATR were detected in six of the eight HL cell lines and in three of the seven clinical cases, most of which displayed a delay/abrogation in the repair of DNA double-strand breaks (DSBs) and single-strand breaks (SSB), as well as a defect in p53 accumulation.…”
Section: Advances In the Understanding Of Molecular Mechanisms Of mentioning
confidence: 99%
“…Noteworthy, most clonal alterations detected were gains in highly recurrent genomic locations containing driver genes such as PD-L1/PD-L2 and REL , while subclonal alterations in examined cases were mainly losses in regions containing tumor suppressors ( TNFAIP3 and CDKN1A ) and genes associated with DNA repair ( ATR ). ATR has already been proposed to have a role in lymphomagenesis in HL as deletions and insertions in the gene have been shown to cause a delay/abrogation in double-strand break and single-strand break repair and defects in the accumulation of p53 14 . Late mutations in cancer genes involved in maintenance of genome integrity through DNA damage response and repair have already been observed also in other cancer types, and it has been proposed that such mutations may provide advantages to emerging subclones later in evolution 15 .…”
mentioning
confidence: 99%